MANAGEMENT SYSTEM FAILOVER DENGAN ROUTING DINAMIS OPEN SHORTEST PATH FIRST DAN BORDER GATEWAY PROTOCOL - Bakhtiar Rifai; Eko Supriyanto (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
No one internet service providers can guarantee 100 % or never experienced disturbance distribution at a customer internet connection. Hence to deliver services internet connection a stable and avoid any way down the customer, generally internet providers having two or more link at customer them to one of them was used as secondary links or backup during the primary had a link. The process of primary switching link to backup it is called failover or redundant link. According to many systems, failovers applied to network an internet among other providers by means of technology routing dynamic OSPF ( open shortest path first ) and BGP (border gateway protocol). Routing was a process to send data from one network to another network. With dynamic routing then routing mechanism is done in dynamic by determining the shortest distance quickly and accurately between equipment the sender and recipient. Open shortest path first (OSPF) is one of the protocol dynamic routings who uses algorithms link-state to build and calculate the shortest line to all purposes are known. While BGP is a protocol routing the core of the internet is used to perform an exchange of information between network routing. BGP working a way mapped a table IP network pointing to the network that could be made between autonomous system (AS).